If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+7=9(x+8)
We move all terms to the left:
6x+7-(9(x+8))=0
We calculate terms in parentheses: -(9(x+8)), so:We get rid of parentheses
9(x+8)
We multiply parentheses
9x+72
Back to the equation:
-(9x+72)
6x-9x-72+7=0
We add all the numbers together, and all the variables
-3x-65=0
We move all terms containing x to the left, all other terms to the right
-3x=65
x=65/-3
x=-21+2/3
| 6(d+6)=90 | | 7x+6x=7 | | 11=2w-21 | | w-1.9=7.78 | | -7x+10=9x+18 | | 9j1+23=86 | | -8(x-5)=16 | | X^2-Id+6=0 | | 53=2u+15 | | 11c+1+36=180 | | 4=(3y+13) | | x-1=35 | | 8-7m^2=-34 | | 6(y-80)=72 | | 3u-6=10u-69 | | 2p+135+3p+3p=540 | | 202500=250000(1+x/100)^2 | | 7x-1+2x+6+3x-7=180 | | k−904=2 | | 890-16x=0 | | 4=24-4h | | 42x+5=65 | | x÷54=7x | | 890-16x=1322-25x | | x+4+3x+11=7x-18 | | 6(y−80)=72 | | 4=24−4h | | w+40=3w | | x÷54=7 | | 5(g-77)=35 | | p+48=3p | | 6y+9=3(2y |